The Minerals Industry And Sustainable Development. Are We Talking To The Right People - Are We Sending The Right Message? - K. Nielsen (Society for Mining, Metallurgy & Exploration, 2007)
The paper uses three examples to illustrate the challenges that the minerals industry is facing with regard to our image and the public?s perception of us. The paper then discusses communication with stakeholders as opposed to lecturing to the public and the authorities, and states that the industry needs to work more directly towards politicians and regulators as target groups. The conclusion is that we still have a way to go before the industry is doing enough to bring our message to the right people, but we are improving.